D’une version du texte à l’autre : aperçus sur la morphographie et sa révision en production verbale écrite - Cogis Danièle; Leblay Christophe (Publizon, 2022)
Studies either in online writing or in draft versions of text have shown that pupils make changes from one version to another while writing a story or a report. Some of these changes concern orthography. In this article, we have examined a sample of written texts from the corpus named Grenouille (i.e. frog) with a double approach, genetic and linguistic. We have focused on plural marks in order to view in detail the revision process in the written texts of pupils from 3rd to 8th grades with different levels of ability. The originality of this work (or its difficulty) lies in the question of how to confront the viewpoints of researchers belonging to different fields in relation to written language production.